Integrated Evaluation of Adipokines, Cardiac Biomarkers, and Autonomic Nervous System Activity in Patients with Metabolic Syndrome: A Cross-Sectional Clinical Study - Zafar Abdul Nabi, Sham Lal Prithiani, Asma Hameed, Syeda Nosheen Zehra, Ambreen Anjum, Ali Ejaz, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Metabolic syndrome (MetS) is a cluster of interrelated cardiometabolic risk factors that significantly increase the likelihood of cardiovascular disease. Recent evidence highlights the roles of adipokines, cardiac biomarkers, and autonomic dysfunction in the pathophysiology of MetS. Objective: To evaluate the integrated relationship between serum adipokines, cardiac biomarkers, and autonomic nervous system function in patients with MetS. Methodology: This cross-sectional study included 100 patients diagnosed with MetS as per IDF criteria. Serum levels of adipokines (leptin, adiponectin, resistin), cardiac biomarkers (troponin I, NT-proBNP, CK-MB), and heart rate variability (HRV) parameters were assessed. Statistical correlations between biochemical parameters and autonomic function indices were analyzed. Results: Elevated leptin and resisting levels, along with reduced adiponectin, were significantly associated with abnormal cardiac biomarkers and impaired HRV indices (p < 0.05). A strong inverse correlation was observed between adiponectin and NT-proBNP (r = -0.42), while leptin positively correlated with reduced HRV time-domain measures. Conclusion: This study suggests a strong interplay between adipokine dysregulation, cardiac stress, and autonomic dysfunction in MetS patients. Integrated biomarker evaluation may offer a promising approach for early cardiovascular risk stratification in this high-risk population. Keywords: Metabolic Syndrome, Adipokines, Cardiac Biomarkers, Heart Rate Variability, Autonomic Dysfunction, Cross-Sectional Study.